'Delayed Disclosure': National Security, Whistle-Blowers and the Nature of Secrecy. (May 2019) - Aldrich, Richard J; Moran, Christopher R
The significance of Edward Snowden's revelations has been viewed primarily through the prism of threats to citizen privacy. Instead, we argue that the most dramatic change has been a decline of government secrecy, especially around national security. While the ethical aspects of state secrets and 'whistle-blowing' have received recent attention, few have attempted to explain the dynamics of this growing climate of exposure. Our argument is largely technological and we ground our analysis in the changing nature of intelligence work, which is increasingly merging with 'big data'. But we also identify a related cultural change: many intelligence contractors are at best agnostic about the national security state. Meanwhile, the Internet itself provides the perfect medium for the anonymous degradation of secrets. Because the main driver is technology, we suggest this trend is likely to accelerate, presenting national security chiefs with one of their biggest future challenges.